Review of North European species of the genus Lathrolestes (Hymenoptera, Ichneumonidae) with description of one new species from Öland (Sweden) - Reshchikov, Alexey (Zootaxa, 2015)
The genus Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Northern Europe is reviewed. A new species, L. oelandinus sp. n. from Öland (Southern Sweden) is described. Illustrated diagnoses for 23 Northern European species are provided. Lathrolestes soperi Reshchikov, 2010 is recorded for the first time in the Palaearctic region (from the UK) and L. bipunctatus (Bridgman, 1886), L. citreus (Brischke, 1878), L. clypeatus (Zetterstedt, 1838) are new records for Denmark, and L. moravicus Habermehl, 1923 is a new record for Finland, France and Russia. Additionally L. ensator recorded newly from Belorus, L. erythrocephalus from Azerbaijan, L. macropygus and L. pictilis from Austria. Trophic interactions of the genus are discussed.